2021
DOI: 10.3390/ijms222112021
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Nanohydroxyapatite Graft and Other Bone Grafts in the Repair of Periodontal Infrabony Lesions: A Systematic Review and Meta-Analysis

Abstract: Objective: To compare the results of periodontal infrabony lesions treated using nanohydroxyapatite (NcHA) graft with other bone grafts (BGs). Methods: Four electronic databases were searched including PubMed (NLM), Embase (Ovid), Medline, and Dentistry and Oral Sciences (EBSCO). The inclusion criteria included randomised controlled clinical trials (RCTs) and controlled clinical trials (CCTs). The clinical results of NcHA were compared with other BGs. For clinical attachment level (CAL) gain, probing pocket de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Research is being carried out in the field of bone regeneration for periodontal defects. Guided tissue regeneration (GTR) procedures [ 52 , 53 , 54 ], the use of enamel matrix derivatives (EMD) [ 55 , 56 , 57 , 58 ], growth factors (GF) [ 59 , 60 , 61 ], BMPs [ 62 ], platelet-rich plasma/fibrin (PRP/PRF) [ 63 , 64 , 65 ], and various bone grafting procedures [ 66 , 67 , 68 , 69 ] have been extensively described in the literature. Autogenous material obtained from the same individual is always considered the gold standard because of its high osteogenic, osteoinductive, and osteoconductive potential [ 70 ].…”
Section: Clinical Applications Of Auto-bgmentioning
confidence: 99%
“…Research is being carried out in the field of bone regeneration for periodontal defects. Guided tissue regeneration (GTR) procedures [ 52 , 53 , 54 ], the use of enamel matrix derivatives (EMD) [ 55 , 56 , 57 , 58 ], growth factors (GF) [ 59 , 60 , 61 ], BMPs [ 62 ], platelet-rich plasma/fibrin (PRP/PRF) [ 63 , 64 , 65 ], and various bone grafting procedures [ 66 , 67 , 68 , 69 ] have been extensively described in the literature. Autogenous material obtained from the same individual is always considered the gold standard because of its high osteogenic, osteoinductive, and osteoconductive potential [ 70 ].…”
Section: Clinical Applications Of Auto-bgmentioning
confidence: 99%
“…The loss of supporting AB surrounding a tooth causes tooth mobility and displacement, ultimately leading to tooth loss [ 1 ]. Numerous approaches, such as BRGs [ 5 , 6 , 7 , 8 , 139 ], scaffolds [ 140 ], stem cells [ 141 ], and growth factors [ 9 , 10 ], have been developed to improve the osteogenesis process. BRGs are usually classified into four types [ 93 , 142 ].…”
Section: Regenerative Mechanisms Of Periodontal Tissuesmentioning
confidence: 99%
“…While traditional periodontal and/or surgical therapies are typically effective in limiting disease development, they cannot repair destroyed periodontal tissue or restore its functioning. Despite the use of different regenerative treatments, such as guided tissue regeneration therapy (GTR) [ 3 , 4 ], bone replacement grafts (BRGs) [ 5 , 6 , 7 , 8 ], multiple growth factor-based treatment [ 9 , 10 ], and enamel matrix derivative [ 11 , 12 , 13 ], the results are sometimes disappointing, with poor clinical predictability.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the addition of 2% nano-HAP can prevent hypersensitivity significantly. A recent systematic review and meta-analysis have compared nano-HAP graft and other bone grafts in the repair of periodontal infrabony lesions, which showed that nano-HAP has equivalent effects to other bone grafts in terms of clinical attachment level gain, probing pocket depth decrease, and gingival recession changes [64]. Therefore, nano-HAP may have a great clinical application prospect in periodontal regeneration.…”
Section: Technological Evolutions: Nano-hap Aggregation-based Biobone...mentioning
confidence: 99%